Abundace and Potential of Megabenthos in The Banda Sea Waters Tourism Park in Lonthoir Village, Banda Island, Central Maluku - Dwi Rosalina; Anisa Aulia Sabilah; Yasser Arafat; Muchtar Amiluddin; A Sri Dewi Syamsul (Jurnal Kelautan, 2023)
ABSTRACTMegabenthos are benthic biota with a size of more than 1 cm and are found living on the bottom of the water, either in coral reef or seagrass ecosystems. Megabenthos also provides benefits to the economy of the surrounding community. This research was conducted in the Banda Sea Tourism Park Area, Lonthoir Village, Banda Islands, Central Maluku, from February 11th to April 21st, 2022. This study aims to determine the type, abundance, and potential of megabenthos in the Banda Sea Waters Tourism Park. Data collection at the observation station is done using the quadratic linear transect method, which is drawn along 400 meters perpendicular to the sea and 300 meters parallel to the coastline with a quadrant size of 10 x 10 m2 with a distance of 10 m between quadrants and a distance of 30 m between transects. From the results of the research carried out, 6 classes of Megabenthos were found, namely Gastropoda, Bivalvia, Holothoroidea, Asteroidea, Echinoidea, and Malacostraca. The Gastropoda class is the megabenthos that is most commonly found in the Banda Sea Marine Tourism Park, namely 1118 individuals with an abundance value of 0.072 ind/m2 and a potential value of 8600 ind. while the lowest class is the Asteroidea class with 20 individuals with an abundance value of 0.011 ind/m2 and a potential of 1333 ind and Malacostraca with 9 individuals with an abundance value of 0.011 ind/m2 and a potential of 1350 ind. The high potential for megabenthos in the waters of the Banda Marine Tourism Park can be influenced by the high population of various marine biota.Keywords: Abundance, Banda Sea, Megabenthos, PotentialABSTRAKMegabentos merupakan biota bentik dengan ukuran lebih dari 1 cm dan ditemukan hidup di dasar perairan baik pada ekosistem terumbu karang atau padang lamun. Megabentos juga memberi manfaat terhadap ekonomi masyarakat sekitar. Penelitian ini dilaksanakan di Kawasan Taman Wisata Perairan Laut Banda, Desa Lonthoir, Kepulauan Banda Maluku Tengah pada 11 Februari sampai 21 April 2022. Penelitian ini bertujuan untuk mengetahui jenis, kelimpahan, dan potensi megabentos di Taman Wisata Perairan Laut Banda. Pengambilan data pada stasiun pengamatan dengan menggunakan Metode Transek Linier Kuadrat yang ditarik sepanjang 400 meter tegak lurus ke arah laut dan 300 m sejajar garis pantai dengan ukuran kuadran 10 x 10 m2 dengan jarak 10 m antar kuadran, serta jarak antar transek 30 m. Dari hasil penelitian yang dilakukan, ditemukan 6 kelas Megabentos, yaitu Gastropoda, Bivalvia, Holothoroidea, asteroidea, Echinoidea, dan Malacostraca. Kelas Gastropoda merupakan megabenthos yang paling banyak ditemukan di Taman Wisata Bahari Laut Banda yaitu sebanyak 1118 individu dengan nilai kelimpahan 0,072 ind/m2 dan nilai potensi 8600 ind. sedangkan kelas terendah ialah Kelas Asteroidea sebanyak 20 individu dengan nilai kelimpahan 0,011 ind/m2 dan potensi 1333 ind dan Malacostraca sebanyak 9 individu dengan nilai kelimpahan 0,011 ind/m2 dan potensi 1350 ind. Tingginya Potensi megabentos diperairan Taman Wisata Laut Banda, dapat berpengaruh dengan tingginya populasi berbagai biota laut.Kata kunci: Kelimpahan, Megabenthos, Potensi, Laut Banda